Should Antibiotic Treatment or Surgery be First-Line for Acute Uncomplicated Appendicitis? A Systematic Review - Farran, Mohamed Ziad; Ong, Shi Yun; Khan, Saad; Ghani, Aiman Yushaq Abdull; Kashyap, Sathvik Vijaya; Thomas, Rajah Devaprasad (Trinity Student Medical Journal, 2024)
Background: Acute appendicitis is the sudden inflammation of the vermiform appendix. It is the most common abdominal emergency. Appendicectomy, performed open or laparoscopically, has been the mainstay in the treatment of uncomplicated appendicitis. This technique has numerous advantages, namely the impossibility of recurrence. The use of antibiotic-only treatment for acute appendicitis has associated benefits and risks. Procedure specific complications of appendicectomy such as wound infections and incisional hernias can be avoided. This treatment option is gaining popularity amongst patients due to these potential benefits. Aim: To determine whether appendicectomy or antibiotic treatment is superior as first-line treatment for acute uncomplicated appendicitis. Methods: Several databases were searched to identify published literature relevant to this field of study. The databases used were Cochrane Library, Medline, and PubMed. Articles that reported on trials utilising antibiotics or surgery for the treatment of acute uncomplicated appendicitis were selected and further screened to ensure that they were randomised controlled trials, ‘English full-text articles’ that were published in peer-reviewed journals from the years 2010-2021. Other types of research studies such as case reports and meta-analyses alongside studies that involved participants aged 16 or younger were excluded. Results: The initial search identified a total of 124 studies. Of these studies, 47 duplicates were excluded and the remaining 77 underwent title and abstract screening. From this screening, 20 studies were identified for a full-text study, which led to the inclusion of 10 papers for this review. On review of these studies, all 10 of these random controlled trials compared the outcomes between antibiotics and surgical intervention for the treatment of acute uncomplicated appendicitis. Conclusions: There is insufficient evidence to suggest that antibiotic therapy should replace appendicectomy as first-line treatment for acute uncomplicated appendicitis. However, while antibiotic therapy failed to meet the criteria for superiority compared with appendicectomy in several major studies, consideration should be given to the other advantages of antibiotic therapy, especially in resource-poor countries, where it can be used to free up hospital beds for emergencies that warrant greater care and intervention.